Antibacterial Activity of Ethanol Extract of Red Betel Leaves (Piper crocatum) and Its Fractions against Escherichia coli pBR322 - Fernanda Chairunisa; Mega Safithri; Maria Bintang (Current Biochemistry, 2022)
Red betel leaf (Piper crocatum) is one of the typical Indonesian herbal plants that has an antibacterial function. This study aimed to test and measure the activity of 70% ethanol extract of red betel leaf and its fractions (n-hexane, ethyl acetate, and water fractions) as antibacterial against specific bacteria Escherichia coli pBR322 based on activity and minimum inhibitory concentration. Extraction was carried out using the maceration method and continued with fractionation based on the level of solvent polarity. Antibacterial activity was indicated by the presence of inhibition zones. The minimum inhibitory concentration was indicated by the appearance of the inhibition zone at the minimum concentration. Results showed that extraction process resulted in crude extract yield of 19.49%. The best antibacterial activity was shown by 1000 ppm n-hexane fraction with an inhibition zone of 2.40 mm ± 0.14. The best minimum inhibitory concentration was 100 ppm n-hexane fraction with an inhibition zone of 0.60 mm ± 0.56.